ESSAYS IN ECONOMETRICS: ONLINE LEARNING IN HIGH-DIMENSIONAL CONTEXTS AND TREATMENT EFFECTS WITH COMPLEX AND UNKNOWN ASSIGNMENT RULES - CLAUDIO CARDOSO FLORES (2021)
PONTIFÍCIA UNIVERSIDADE CATÓLICA DO RIO DE JANEIRO